Selection and Validation of Reference Genes for qRT-PCR in Cycas elongata. - Yanting Hu; Tian Deng; Letian Chen; Hong Wu; Shouzhou Zhang (PLoS ONE, 2016)
Quantitative reverse transcription PCR (qRT-PCR) is a sensitive technique used in gene expression studies. To achieve a reliable quantification of transcripts, appropriate reference genes are required for comparison of transcripts in different samples. However, few reference genes are available for non-model taxa, and to date, reliable reference genes in Cycas elongata have not been well characterized. In this study, 13 reference genes (ACT7, TUB, UBQ, EIF4, EF1, CLATHRIN1, PP2A, RPB2, GAPC2, TIP41, MAPK, SAMDC and CYP) were chosen from the transcriptome database of C. elongata, and these genes were evaluated in 8 different organ samples. Three software programs, NormFinder, GeNorm and BestKeeper, were used to validate the stability of the potential reference genes. Results obtained from these three programs suggested that CeGAPC2 and CeRPB2 are the most stable reference genes, while CeACT7 is the least stable one among the 13 tested genes. Further confirmation of the identified reference genes was established by the relative expression of AGAMOUSE gene of C. elongata (CeAG). While our stable reference genes generated consistent expression patterns in eight tissues, we note that our results indicate that an inappropriate reference gene might cause erroneous results. Our systematic analysis for stable reference genes of C. elongata facilitates further gene expression studies and functional analyses of this species.